Quien fue Abraham Lincoln? - Pascal, Janet B.; O'Brien, John, 1953- (New York : Grosset & Dunlap, 2012)
Looks at the life of Abraham Lincoln, a farmer boy who grew up to become the sixteenth president of the United States and the man responsible for leading the country through the Civil War.
Translation of: Who was Abraham Lincoln?
Includes bibliographical references (p. 104)
Text in Spanish.
Keywords: Lincoln, Abraham, -- 1809-1865.; Presidents -- United States -- Biography; Presidents; Spanish language materials